Oxidative stress in retinal pigment epithelium impairs stem cells: a vicious cycle in age-related macular degeneration - Lazzarini, Raffaella; Nicolai, Michele; Lucarini, Guendalina; Pirani, Vittorio; Mariotti, Cesare; Bracci, Massimo; Mattioli-Belmonte, Monica (Molecular and cellular biochemistry, 2022)
Aging, chronic oxidative stress, and inflammation are major pathogenic factors in the development and progression of age-related macular degeneration (AMD) with the loss of retinal pigment epithelium (RPE). The human RPE contains a subpopulation of progenitors ( i.e. , RPE stem cells—RPESCs) whose role in the RPE homeostasis is under investigation. We evaluated the paracrine effects of mature RPE cells exposed to oxidative stress (H 2 O 2 ) on RPESCs behavior through co-cultural, morphofunctional, and bioinformatic approaches. RPESCs showed a decline in proliferation, an increase of the senescence-associated β-galactosidase activity, the acquisition of a senescent-like secretory phenotype (SASP), and the reduction of their stemness and differentiation competencies. IL-6 and Superoxide Dismutase 2 (SOD2) seem to be key molecules in RPESCs response to oxidative stress. Our results get insight into stress-induced senescent-associated molecular mechanisms implicated in AMD pathogenesis. The presence of chronic oxidative stress in the microenvironment reduces the RPESCs abilities, inducing and/or maintaining a pro-inflammatory retinal milieu that in turn could affect AMD onset and progression.